Different inflammation responses modulate Müller glia proliferation in the acute or chronically damaged zebrafish retina - Iribarne, Maria; Hyde, David R. (Frontiers in Cell and Developmental Biology, 2022)
Unlike mammals, zebrafish regenerate in response to retinal damage. Because microglia are activated by retinal damage, we investigated their role during regeneration following either acute or chronic damage. At three weeks post-fertilization (wpf), both wild-type fish exhibiting NMDA-induced acute ganglion and amacrine cell death and gold rush (gosh) mutant fish possessing chronic cone photoreceptor degeneration displayed reactive microglia/macrophages and Müller glia proliferation. Dexamethasone-treated retinas, to inhibit the immune response, lacked reactive microglia/macrophages and possessed fewer PCNA-positive cells, while LPS treatment increased microglia/macrophages and PCNA-labeled cells. NMDA-injured retinas upregulated expression of il-1β and tnfα pro-inflammatory cytokine genes, followed by increased expression of il-10 and arg1 anti-inflammatory/remodeling cytokine genes. A transient early TNFα pro-inflammatory microglia/macrophage population was visualized in NMDA-damaged retinas. In contrast, gosh mutant retinas exhibited a slight increase of pro-inflammatory cytokine gene expression concurrently with a greater increased anti-inflammatory/remodeling cytokine gene expression. Few TNFα pro-inflammatory microglia/macrophages were observed in the gosh retina. Understanding why acute and chronic damage results in different inflammation profiles and their effects on regulating zebrafish retinal regeneration would provide important clues toward improving therapeutic strategies for repairing injured mammalian tissues.